Emotions and Values of Female Characters in the Old Testament - Irena Avsenik Nabergoj (Edinost in Dialog, 2023)
This paper, taking into account previous partial studies, formulates the methodology, aspects, and aims of a pioneering study of emotions in all the major literary genres of the Old Testament books. Special attention is given to the literary representation of the emotional state of female characters in Old Testament narratives and poems. In light of previous representations of emotions in the Old Testament, the study proposes an integrated analysis of the selected texts that combines linguistic-literary, historical-anthropological, and ethical-moral aspects. The focus is on the study of emotions in the relationships between male and female persons and between humans and God. The analysis of the selected texts takes into account the broader textual and intertextual relationships in relation to similar texts in the Old Testament. The paper focuses on how partial, often abstractly cognitive and allegorical methods can be complemented by a more holistic approach at both the diachronic and synchronic levels in assessing the authenticity of the emotions of the acting subjects. From a methodological point of view, it is also important to pay attention to the relationships between the explicit and implicit representation of the emotions of the main and secondary characters.